New Zealand : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This Selected Issues paper analyzes whether cyclical factors, including the large real exchange rate appreciation in recent years in New Zealand, can account for the rapidity of the recent rise in import penetration, or whether more lasting structural changes, such as the effects of globalization, may have played a role. The paper also looks at New Zealand's vulnerabilities from two angles. It evaluates the external position of the country, and then assesses the health and soundness of various sectors of the economy by looking at their balance sheets and the key vulnerability indicators.